SEJARAH KODIFIKASI HUKUM ISLAM (TAQNIN) DI NEGARA ISLAM - Misnan Misnan (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2021)
Taqnin is an incorporation of Islamic law (fiqh) into a state legal system. The enacted Islamic law has a binding legal force and therefore must be obeyed all citizens. Since introduced by ‘Ibn Muqaffa’ in the reign of the abbasid caliph, the development of taqnin had experienced ups and downs. The taqnin was truly realized, when the Majallah al-Ahkam al-Adhliyah was implemented throughout the Ottoman Empire in 1293 AH/1878 AD. This paper discusses the history of the development of taqnin in Muslim countries, including Indonesia.